Breaking down barriers for hepatitis B screening in the Bronx West African community through education in collaboration with faith-based organizations: A cohort study - Emmanuel U. Emeasoba; Fatima Omarufilo; John Nnaemeka Bosah; Samuel H. Sigal (Elsevier, 2022)
Summary: Background: Many residents of the Bronx are from West Africa where chronic hepatitis B is endemic. Hepatitis B screening is low in West African immigrant communities due to multiple possible cultural and socioeconomic factors. Methods: A culturally sensitive educational program on hepatitis B with a special emphasis on the relevance for the West African community was developed. Arrangements were made with leaders of West African faith-based organizations to conduct educational programs following religious services after which a survey was completed to assess changes in attitudes towards the infection and motivation for testing. Arrangements were then made for serologic testing at which time hypertension screening was also performed. Findings: Nine events in which a total of 550 people attended were held. Among the 339 (61.6%) participants who completed the questionnaire, 325 of the participants (95.1%) reported improved understanding, and 236 (67.0%) indicated greater comfort in sharing a meal and talking with an infected individual. Two hundred seventy-four participants (82.7%) indicated an intention to undergo testing, and 339 (97.8%) indicated that they would encourage family and friends to undergo screening. Three hundred thirty-two of the 550 participants (60.3%) requested serologic testing. Among those requesting testing, 224 (67.5%) underwent testing. Interpretation: A culturally sensitive educational program in collaboration with faith-based organizations is effective in motivating people from West Africa to undergo screening for hepatitis B at which time other preventative health care measures such as hypertension screening can be performed. Funding: Check Hep B Navigation Program funded by the New York Council, Gilead Sciences, Albert Einstein College of Medicine Global Health Center and generous donations by Friends and Family of Jason Marks and the 41-74 Club of NY. Bayan: XXX. fage: Yawancin mazauna Bronx sun fito ne daga Yammacin Afirka inda cutar hepatitis B ke ci gaba da yaduwa. Binciken hepatitis B yana da karanci a cikin al'ummomin baƙi na Yammacin Afirka saboda yuwuwar abubuwan al'adu da na tattalin arziƙi. Hanyoyi: An haɓaka wani shirin ilmantarwa na al'adu kan cutar hepatitis B tare da ba da fifiko na musamman ga dacewa ga al'ummar Yammacin Afirka. An yi shiri tare da shugabannin ƙungiyoyin addinan Afirka ta Yamma don gudanar da shirye-shiryen ilimi bayan ayyukan addini bayan haka aka kammala bincike don tantance halaye game da kamuwa da cutar da himma don gwaji. Sannan an yi shirye -shirye don gwajin serologic wanda a lokacin ne kuma aka yi gwajin hawan jini. Sakamakon: An gudanar da abubuwa tara wanda jimlar mutane 550 suka halarta. Daga cikin mahalarta 339 (61.6%) da suka kammala tambayoyin, 325 daga cikin mahalarta (95.1%) sun ba da rahoton ingantacciyar fahimta, kuma 236 (67.0%) sun nuna ƙarin ta'aziyya wajen raba abinci da yin magana da mai cutar. Mahalarta ɗari biyu da saba'in da huɗu (82.7%) sun nuna niyyar yin gwaji, kuma 339 (97.8%) sun nuna cewa za su ƙarfafa dangi da abokai don yin gwajin. Dari uku da talatin da biyu daga cikin mahalarta 550 (60.3%) sun buƙaci gwajin serologic. Daga cikin wadanda ke neman gwaji, 224 (67.5%) sun yi gwaji. Fassara: shirin ilmantarwa mai mahimmanci na al'adu tare da haɗin gwiwar ƙungiyoyi masu imani suna da tasiri wajen motsa mutane daga Yammacin Afirka don yin gwajin cutar hepatitis B a lokacin da za a iya yin wasu matakan kula da lafiya kamar rigakafin hawan jini. Kuɗi: Shirin Hep B Navigation Programme wanda Majalisar New York, Kimiyya ta Gilead, Cibiyar Kiwon Lafiya ta Duniya ta Albert Einstein da Cibiyar Kyauta ta Abokai da Iyalan Jason Marks da 41-74 Club na NY suka bayar.